Auditoría De Gestión Del Inventario Y Su Incidencia En La Toma De Decisiones En El Supermercado “Polita”, Cantón Buena Fe, Año 2023 - Montecé Miranda, Víctor Manuel (2025)
The objective of this research is to conduct an inventory management audit in the “POLITA” supermarket and analyze its impact on decision making. It examines the relationship between inventory management and the effectiveness of internal control processes, evaluating how this influence operational efficiency and the quality of business decisions. The study considers as its universe the 20 employees of the inventory department, who actively participated in the research. A mixed approach was used for data collection, combining inductive and deductive methods. Several techniques were used, such as direct observation, interviews and surveys, allowing to obtain both qualitative and quantitative information. The results show that the supermarket has limitations in the evaluation of the impact of its inventory management. The audit, based on the COSO I model, reveals a confidence level of 73.72%, which indicates poor management with a risk of 26.28%, re flecting moderate-high compliance. In addition, the findings identify the lack of clear documentation on the responsibilities of each area, the absence of continuous training for staff and the lack of a formal system for updating information, which affects the efficiency of internal processes.